A parent-based book-reading intervention for disadvantaged children with language difficulties. (February 2014) - Colmar, Susan Hilary
Children with delayed language skills, who were from a socio-economic area defined as disadvantaged, made significant improvements in language skills after their parents were trained in easily learned strategies, enabling them to make simple changes in the way they interacted with their children. The 36 children, mean age five years, were allocated into three groups: an Experimental group and a Control group, where all the children had language delays and/or difficulties, and a second Control group of children whose language was measured within the average range. Parents of children in the Experimental group were trained and asked to implement the strategies. The intervention strategies used during book reading and during everyday conversations included: pausing and encouraging the child to talk more on their chosen topic, over a four-month period. Using an ANCOVA on difference scores with children's pre-intervention language scores for each variable as the covariate, significant results were obtained at post testing. Further, large effect sizes were measured using Cohen's d . In addition, a Student–Newman–Keuls test on difference scores confirmed that the significant changes were obtained for the Experimental group, as predicted.